1999
DOI: 10.1089/thy.1999.9.85
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Function in Very Preterm Newborns: Possible Implications

Abstract: Thyroid hormones are essential for brain maturation. Very preterm infants, who are at risk of neurodevelopmental disabilities also have low thyroxine (T4) and free thyroxine (FT4) values in the first weeks after birth. This transient hypothyroxinemia may in part be causal to the neurodevelopmental problems. We have carried out a randomized, double-blind, placebo-controlled trial with T4 in 200 infants less than 30 weeks gestation. T4 (or placebo) was given in fixed dose of 8 microg/kg birth weight per day duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
1
2

Year Published

2001
2001
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 30 publications
0
25
1
2
Order By: Relevance
“…This transient hypothyroxinemia may influence certain brain structures, and the degree of postnatal thyroid hormone surge is influenced by gestational age. 17,18 Although the precise relationship with the STN and globus pallidus remains to be established, these maternal and fetal/infant hormones might play some role in the development of these structures and result in the signal intensity changes observed on MR imaging in the present study. Normal signal intensity changes also are seen in other parts of the brain such as anterior pituitary lobe that also depends on postnatal age.…”
Section: Discussionmentioning
confidence: 75%
“…This transient hypothyroxinemia may influence certain brain structures, and the degree of postnatal thyroid hormone surge is influenced by gestational age. 17,18 Although the precise relationship with the STN and globus pallidus remains to be established, these maternal and fetal/infant hormones might play some role in the development of these structures and result in the signal intensity changes observed on MR imaging in the present study. Normal signal intensity changes also are seen in other parts of the brain such as anterior pituitary lobe that also depends on postnatal age.…”
Section: Discussionmentioning
confidence: 75%
“…Preterm serum T 4 and FT 4 concentrations are lower than those of term infants, but the TSH concentrations are comparable to term infants. 49,50 Serum TBG concentrations are only slightly low in preterm infants and do not account for the degree of hypothyroxinemia. Consequently, the FT 4 is rarely as low as the total T 4 .…”
Section: Low T 4 and Normal Tsh Valuesmentioning
confidence: 99%
“…In an earlier study, we found higher heart rates in children who received only T 4 (23). For studying the effects of T 3 plus T 4 administration on the cardiovascular system, intra-arterial blood pressure, heart rates, and cumulative doses of inotropic agents were measured in all infants included in the current study.…”
mentioning
confidence: 92%